Characterization of the antioxidant activity, carotenoid profile by HPLC-MS of exotic Colombian fruits (goldenberry and purple passion fruit) and optimization of antioxidant activity of this fruit blend (2023)
ABSTRACT: The consumption of antioxidants can prevent chronic non-communicable diseases and the exotic Colombian fruits, goldenberry (Physalis peruviana L.) and purple passion fruit (Passiflora edulis f. Edulis Sims), are rich in bioactive compounds. The aim of this work was to characterize and optimize the antioxidant activity of these fruits blend. The fruits were classified according to their maturity stages, the freeze-dried extracts were physiochemically characterized, and polyphenols, carotenoids and antioxidant activity were quantified, and an experimental mixture design was applied to optimize the antioxidant activity of the bend. For the goldenberry the maturity stage 3 had higher iron-reducing capacity and higher content of polyphenols. Meanwhile, for the purple passion fruit, this maturity stage had higher antioxidant activity by all methodologies and a higher concentration of polyphenols; the ultrasound-assisted extraction showed statistical differences for polyphenols, ABTS and FRAP. Antioxidant activity showed significant differences (p < 0.05) between samples (TBARS (3.98 ± 0.14 and 7.03 ± 0.85 μM-MDA/g), ABTS (36.53 ± 2.66 and 29.4 ± 4.88 μMTrolox/g), DPPH (36.53 ± 2.66 and 23.90 ± 0.96μMTrolox/g), ORAC (23.02 ± 0.36 and 32.44 ± 0.94 μM Trolox/g) and total polyphenols (5, 29 ± 0.34 and 9.12 ± 0.37mgGA/g). Some of the carotenoids identified by HPLC-MS in both fruits were lutein, α and β-carotene, phytoene and lycopene. The optimum bend was goldenberry 0.83 and purple passion fruit 0.17.